-5(v+3)+3v+7=8v+7

Simple and best practice solution for -5(v+3)+3v+7=8v+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(v+3)+3v+7=8v+7 equation:


Simplifying
-5(v + 3) + 3v + 7 = 8v + 7

Reorder the terms:
-5(3 + v) + 3v + 7 = 8v + 7
(3 * -5 + v * -5) + 3v + 7 = 8v + 7
(-15 + -5v) + 3v + 7 = 8v + 7

Reorder the terms:
-15 + 7 + -5v + 3v = 8v + 7

Combine like terms: -15 + 7 = -8
-8 + -5v + 3v = 8v + 7

Combine like terms: -5v + 3v = -2v
-8 + -2v = 8v + 7

Reorder the terms:
-8 + -2v = 7 + 8v

Solving
-8 + -2v = 7 + 8v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-8v' to each side of the equation.
-8 + -2v + -8v = 7 + 8v + -8v

Combine like terms: -2v + -8v = -10v
-8 + -10v = 7 + 8v + -8v

Combine like terms: 8v + -8v = 0
-8 + -10v = 7 + 0
-8 + -10v = 7

Add '8' to each side of the equation.
-8 + 8 + -10v = 7 + 8

Combine like terms: -8 + 8 = 0
0 + -10v = 7 + 8
-10v = 7 + 8

Combine like terms: 7 + 8 = 15
-10v = 15

Divide each side by '-10'.
v = -1.5

Simplifying
v = -1.5

See similar equations:

| 15.4+2*5.3= | | 10y-7=19y+65 | | 6=8+x | | -3(4y-6)-y=4(y-5) | | 15x^2-58x+48=0 | | M=-5(2) | | 58/18-1/3 | | 3b-8.04=4.77 | | (x)2-10x+16=0 | | 3x*7(3x+4)= | | k-4+6=-2 | | -2(x+1)=-14 | | 6p-7(6+7p)=-128 | | 1.2*(4+3)-7= | | 3t^2+4/t=3t+4 | | -8(m+1)-m-9=-9(m+3)+10 | | 13r+5r= | | 9/(7x+3)-(42y/6)+10(5z) | | 10y-7=19y+72 | | -12-v=v-2 | | -12=8+f-2 | | 5/2x+2 | | 7m+2m+5p+4m= | | 2(lh+wh)=a | | 2[3+4(5-3)]= | | 18-5b=3(b+8)+10 | | a=bnx | | 2m-1+3m+6=4m+9 | | 2x+2x+16+2x=172 | | (2x^3-4x^2+2)/2x-2 | | t-6-3=8 | | 2x+156=156 |

Equations solver categories